Comparison of the dehydration kinetics of solid state compounds of 2-methoxybenzylidenepyruvate with some divalent metal ions - Kobelnik, M. [UNESP]; Ribeiro, C. A. [UNESP]; Dias, D. S. [UNESP]; Bernabé, G. A. [UNESP]; Crespi., M. S. [UNESP] (Ecletica Quimica, 2010)
Divalent metal complexes of ligand 2-methoxybenzylidenepyruvate with Fe, Co, Ni, Cu and Zn as well as sodium salt were synthesized and investigated in the solid state. TG curves of these compounds were obtained with masses sample of 1 and 5mg under nitrogen atmosphere. Different heating rates were used to characterize and study these compounds from the kinetic point of view. The activation energy and pre-exponential factor were obtained applying the Wall-Flynn-Ozawa method to the TG curves. The obtained data were evaluated and the values of activation energy (Ea / kJ mol-1) was plotted in function of the conversion degree (á). The results show that due to mass sample, different activation energies were obtained. The results are discussed mainly taking into account the linear dependence between the activation energy and the pre exponential factor, where was verified the effect of kinetic compensation (KCE) and possible linear relations between the dehydrations steps of these compounds.
Keywords: 2-methoxybenzylidenepyruvate; Bivalent metal ions; Dehydration; Non-isothermal kinetics